Pengaruh Penggunaan Video Animasi Terhadap Peningkatan Keterampilan Menyimak Teks Cerita Rakyat (INDONESIAN LANGUAGE TEACHING & LITERATURE JOURNAL, 2023)
This study aims to describe the effect caused after using animated video-based learning media on class X students of SMK Negeri 6 Pangkep. This research is a pre-experimental research with a quantitative approach, the population in this study were all students of class X SMK Negeri 6 Pangkep. Data collection techniques in this study were written tests and data analysis techniques, namely normality tests and hypothesis tests using the SPSS 23 computer program: student learning outcomes before using animated videos obtained an average value of 30.86. Student learning outcomes after using animated videos obtained an average value of 72.90. The use of animated videos can be concluded to have an effect on improving listening skills and learning outcomes of class X students of SMK Negeri 6 Pangkep in the 2022/2023 school year.